2022
DOI: 10.1039/d2cp01530g
|View full text |Cite
|
Sign up to set email alerts
|

Long-ranged heterogeneous structure in aqueous solutions of the deep eutectic solvent choline and geranate at the liquid–vapor interface

Abstract: The deep eutectic solvent choline and geranate (CAGE) has shown promise in many therapeutic applications. CAGE facilitates drug delivery through unique modes of action making it an exciting therapeutic option....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Each system consisted of infinitely repeated cells with periodic boundary conditions extending in all three directions. Interfaces are introduced following the scheme described by Felipe et al This work focuses on introducing our method, not examining these systems, so we leave in-depth description to other studies. However, some description of the systems helps to provide context for the utility of this method and the results we report.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each system consisted of infinitely repeated cells with periodic boundary conditions extending in all three directions. Interfaces are introduced following the scheme described by Felipe et al This work focuses on introducing our method, not examining these systems, so we leave in-depth description to other studies. However, some description of the systems helps to provide context for the utility of this method and the results we report.…”
Section: Methodsmentioning
confidence: 99%
“…This liquid−vacuum system was previously reported by Felipe et al and is shown in Figure 5b. 9 The simulation contained 1000 water molecules, 400 geranic acid molecules, 400 choline cations, and 400 geranate anions. Collectively, geranic acid, choline, and geranate are sometimes called CAGE.…”
Section: Search Cone Length Hmentioning
confidence: 99%
See 1 more Smart Citation
“…It can solubilize both hydrophobic and hydrophilic drugs and can be used in the delivery of proteins and nucleic acids [ 28 ]. CAGE has numerous therapeutic applications as it facilitates drug delivery owing to its unique properties, making it an interesting therapeutic drug delivery system [ 29 ]. Numerous IL/DES and API/DES combinations and their applications in the pharmaceutical sciences are highlighted in Table 1 .…”
Section: Deep Eutectic Systems (Des)mentioning
confidence: 99%
“…A few computational models of the structure at the gas/DES interface provide beneficial information for gas capture and separation technologies. , Aparicio et al noted that the HBDs in choline chloride:2 urea and choline chloride:malonic acid (318 K, 0.1 MPa) are oriented parallel to the gas/DES interface. The HBD in choline chloride:2 glycerol is oriented slightly off parallel, although an exact angle was not provided .…”
Section: Computational Modeling Of Interfacial and Bulk Structure In ...mentioning
confidence: 99%